Molecular tools of antibiotic resistance for Helicobacter pylori: an overview in Latin America - Contreras, Monica; Mujica, Heisser; García-Amado, María Alexandra (Frontiers in Gastroenterology, 2024)
Antibiotic resistance in the treatment of H. pylori infection is the principal reason for the failure of eradication regimens using the triple therapy. We reviewed the mechanisms of H. pylori antibiotic resistance and assessed the molecular tools commonly used to detect antibiotic resistance in Latin America. Most commonly reported molecular techniques were PCR and sequencing, as well as its variants PCR-RFLP and qPCR to detect the genes and mutations involved in the resistance to clarithromycin (CLR), amoxicillin (AMX), levofloxacin (LVX), tetracycline (TET), and metronidazole (MTZ). The mutation-associated resistance rates varied from 2.2% to 83.3% for CLA and 12% to 100% for LVX in 7 and 4 countries, respectively, whereas for MTZ the resistance frequency was between 50% to 100% in 4 countries. For TET and AMX, frequency of the resistance was in the range of 0% to 27% (5 and 3 countries, respectively). Molecular tools can be used for the rapid detection of resistance to CLR, LVX, and TET, whereas genotypic analysis is not appropriate to detect resistance to AMX and MTZ due to genomic changes found in the rdxA and pbp1A genes. The revision of the different molecular methods showed that qPCR and RFLP are the best tools to detect the resistance of H. pylori. Few molecular tools have been developed in Latin America to detect H. pylori resistance to antibiotics. More studies would be needed to understand better efficient strategies to prevent further emergence of antimicrobial resistance.